Blockchain, Automation, and AI in Accounting: Challenges, Opportunities, and Global Perspectives - Noviany, Henny; Nurkhasanah, Yeni; Marlina, Siska (Indonesian Scientific Publication, 2025)
Digital transformation represents a significant evolution in the accounting profession, characterized by the integration of artificial intelligence, automation, and blockchain technologies. This study aims to synthesize and critically evaluate current evidence on how these technologies shape accounting practices, professional roles, and organizational processes. The review employed a structured methodology involving multiple academic databases, targeted keywords, and explicit inclusion and exclusion criteria to identify peer-reviewed studies relevant to digital transformation in accounting. The findings indicate that AI adoption improves audit efficiency and reduces costs by automating repetitive processes and enabling advanced analytics. Automation enhances accuracy and timeliness in financial reporting, with large organizations benefiting most from advanced ERP systems, while SMEs rely increasingly on accessible cloud-based solutions. Blockchain contributes to transparency and data integrity through immutable records, but adoption is uneven across regions due to regulatory and infrastructural disparities. The discussion emphasizes that systemic factors—organizational culture, regulatory frameworks, and technological infrastructure—critically influence outcomes, while government incentives, training initiatives, and partnerships with technology providers are key strategies for overcoming adoption barriers. Limitations in the literature include fragmented focus on individual technologies, geographical bias toward developed economies, and insufficient attention to professional identity and ethics. The review concludes that addressing these gaps and promoting inclusive digital strategies are essential for ensuring sustainable transformation in accounting. These findings have significant implications for policymakers, educators, and practitioners seeking to align accounting practices with the demands of the digital era.